Epistemology of Education in the Era of Artificial Intelligence: A Philosophical Study of Science for Future Teachers - Kris Nurnaningsih; Susi Sugiarti; Jenuri Jenuri (Papanda Publisher, 2026)
The integration of Artificial Intelligence (AI) into formal education has fundamentally disrupted the epistemological foundations of learning by altering how knowledge is produced, validated, and authorized. Despite growing scholarship on AI in education, the philosophical dimensions of machine-generated knowledge and their implications for teacher preparation remain theoretically underexplored. This study employs philosophical inquiry supported by a systematic literature review of peer-reviewed sources published between 2014 and 2024 to examine how AI transforms educational epistemology and to develop a conceptual framework for future teachers. The analysis identifies five interrelated epistemic transformations: the emergence of algorithmic knowledge sources, the disruption of traditional validity mechanisms, the redistribution of epistemic authority, the irreducibility of human-centered competencies, and the reconstitution of teacher identity as epistemic curatorship. Together, these findings constitute the AI Educational Epistemology Framework for Future Teachers (AIEFF-FT). The study contributes theoretically by extending existing philosophical accounts of AI and education and practically by providing teacher education programs with a structured model for cultivating epistemological literacy, critical AI evaluation, and philosophical responsibility. Future empirical research is needed to validate the framework across diverse educational contexts.